Analysis Of Debit Of Natural Tourism Flow Water Amarilis City Kendari Provinsi Sulawesi Tenggara - Harudu, La; Eso, Rosliana (UNM Geographic Journal, 2018)
Amarilis waterfall is in the area of Forest Park (Tahura) Nipa-Nipa mountains in addition to serve as a natural tourist spot as well as upstream sources of clean water by people around the flow of waterfalls lasting Â± 30 years. The problem is that in the last two years water entering the community began to blur during the rainy season and reduced, none other than the problem of discharge and many other tourism potentials to be observed by visitors. So the researchers analyzed the flow of waterfall flow Amarilis and identify the potential tourist attraction waterfalls. After measuring the flow of Amarilis waterfall flow of 0.315 m3 / sec (instantaneous measurement). Waterfalls in addition to the potential of natural tourism there is another potential that is; peak viktor camp area, flora there are various types of plants, fauna there are various types of animals and natural panorama that has the appeal of the pengujung and observe the expanse of Kendari and Kendari Bay.Â